Perceptions of stakeholders on the roles of Southern Iloilo Coastal Resource Management Council (SICRMC) - Moreno, Ma. Ines M; Torejo, Sheryl Mae S. (2005.)
This is a descriptive study of the perceptions of stakeholders on the Roles of Southern Iloilo Coastal Resource Management Council. There were one hundred one respondents in the study. They were the Chairman or any officer of the Barangay fisheries Aquatic Resource Management Council (BFARMC), one women involved in fishing, also a member or officer of the BFARMC, and commercial fishers which were obtained from the list of Bureau of Fisheries and Aquatic Resources (BFAR). The study was conducted in five municipalities that covered Panay Gulf namely: Oton, Tigbauan, Guimbal, Miag-ao, and San Joaquin., The study found out that small-scale fishermen and women involved in fishing have the same responses with regards to the program implementation of the council while commercial fishers have different views regarding the roles of the council. This was due to the fact that the programs of the council benefited the small-scale fishermen and the women sector involved in fishing while adversely affects the commercial fishers. Their perception was influenced by their educational attainment, sector involved in , and number of years in fishing.
Thesis (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo
Keywords: Southern Iloilo Coastal Resource management Council; Southern Iloilo Coastal Resource management Council -- Stakeholders